Marketing financial services (Butterworth-Heinemann, 1995)
Within a practical business context of the changing, competitive climate, this book details the implications for marketing strategy. New chapters cover topics such as credit cards and customer care, while several relevant case studies have also been added. Combining analysis of principles, concepts and techniques with sound practical advice, 'Marketing Financial Services' is ideal for students on degree and postgraduate courses, including Chartered Institute of Bankers.